Corporate social innovation as a driver of performance and welfare - Susanna Ulinski (WWWforEurope, 2015)
Social innovation is booming as a political buzzword. However, the concept still lacks scientific analysis, a common epistemology and a clear-cut definition. This thesis takes a step towards a better theoretical and conceptual understanding of corporate social innovation by detaching the concept from the government and NPO sector. It suggests defining social innovation by its social means and social ends. The term "social" not only refers to the non-material nature of innovation and its social process that modifies social practices, behaviour and relationships, but also relates to the achievement of socially desirable ends. The means and ends for corporate social innovation are further analysed in three case studies on carsharing, Fair Trade and diversity management of a multi-ethnic workforce. The analysis also shows that for-profit companies not only play an important role in the advancement of social innovations, but also that social innovations constitute a business opportunity. Moreover, the characteristics of (corporate) social innovations offer our society and economy the dynamics to adapt to social challenges in a complex environment.
Keywords: A14; D02; O39; M14; 330; Social innovation; corporate social innovation; Beyond GDP; institutional change; socio-ecological transition